The effectiveness of reciprocal teaching of reading strategies on ESL students' writing enhancement - Habibi, Hadis (2020)
Since not much consideration has been given, by students and English teachers alike, towards the critical role that reading plays in ESL students' writing enhancement, this study investigated the effect of Reciprocal Teaching Strategies inclusive of predicting, questioning, clarifying and summarizing on ESL students' writing improvement (Ghorbani et al., 2013). It also addresses a need to collect the students' and their English teacher's perceptions (Fisher & Frey, 2007; Stricklin, 2011) towards the use of the four strategies in reciprocal teaching strategies. The researcher of this study selected a mixed quantitative/qualitative research design for data analysis. A total of 104 Malaysian secondary students participated in this study. The instruments used to collect data for this study are CLAWS tagger, AntConc. interviews and Nvivo 10. The outcomes of this study, both quantitatively and qualitatively, revealed the positive impact of reciprocal teaching strategies on participants' writing skills after the intervention. This study has made significant contributions by introducing a new method for boosting ESL students' writing skills; utilizing a computer-based tool for analysing students' classroom writing assignments; creating a new style for essay writing; and providing educational insights to the Ministry of Education, which has always been concerned about Malaysian students' English proficiency.